THE PERFECT BALANCE IN DESIGNS EXECUTED ON ANCIENT IRAQI POTTERY - Muhammad Khudair Abbas, Dr. Hossam Sabah Jurd (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The research problem dealt with the nature of the knowledge of intellectual expansion in the systems of aesthetic creativity and the nature of raw materials taken as components of their structure within the circle of aesthetic balance because it is an art that transforms the artistic and technical form as well as the possibility of its openness to the neighboring rich races. This is what called for the study of the systems of change in the structure of pottery and what constitutes a new reading, and what the research consists of four sections. The general framework of the research is identified with an indication of the importance of its existence. Then, the goal of the research was determined, which is the ideal balance in the designs executed on the ancient Iraqi pottery. Furthermore, the establishment of the three limits of research objective, temporal and spatial. Then, the study defines the terminology related to the title. Moreover, it provides the theoretical framework and the indicators that resulted from the academic theorizing of the subject. The researchers have identified two implicit titles within this framework to ensure reading the topic of the research according to its various definitional frameworks, such as the concept of ideal balance and balance in ancient Iraqi pottery. As for the third chapter, it represented the research procedures, by revealing the studied community and the sample selected from 4 works, then defining the research tool methodology, followed by the analysis of the sample. As for the fourth chapter, it included the results of the research, conclusions and recommendations from it. The acquisition of pottery forms an ideal balance through space, color and line that it forms an integrated visual unity of the whole scene, embodying human forms in the movement of abstract models, which represent the perfect balance in the movement of the upper horizontal of the forms, and giving the perfect balance towards the repetition movement that the artist carried out on the surface of the pottery body.